Applying the scholarship of teaching and learning beyond the individual classroom - Friberg, Jennifer C., 1974-; McKinney, Kathleen (Scholarship of teaching and learning., 2019)
"When the Scholarship of Teaching and Learning (SoTL) emerged, it often concentrated on individual faculty practice in one classroom; it is now, however, increasingly common to find work in SoTL focused more broadly. SoTL studies may engage with a cluster of courses, a program, a particular population of students, a pedagogical approach, or a field--all of which are represented in the essays collected here by authors from a diverse array of institutions and nations. This volume features examples of SoTL research conducted in, and applied to, a variety of contexts and disciplines, offering a theoretical framework for an expanded vision of SoTL--one that moves beyond the individual classroom."--Provided by publisher